Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1159/000244212
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis-Promoting Factor in Human Colostrum

Abstract: The effect of colostrum of mothers of preterm and full-term newborns on the phagocytic activity for latex particles by normal peripheral blood polymorphonuclear cells was examined. The results showed that human colostrum contains a phagocytosis-promoting factor(s), which not only increases the number of phagocytic cells, but also stimulates the phagocytic activity of the individual cell. This factor(s) was more active in preterm colostrum. Thus, while term colostrum increased the number of phagocytic cells by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…This result indicates that phagocytosis-promoting factor(s) are present in bovine colostrum. It has reported that human colostrum has a phagocytosis-promoting factor [21] and colostral mononuclear phagocytes are able to kill enteropathogenic Escherichia coli opsonized with human colostral IgA [22]. Thus, there is a possibility that colostrum possess either opsonizing or stimulating effect on phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that phagocytosis-promoting factor(s) are present in bovine colostrum. It has reported that human colostrum has a phagocytosis-promoting factor [21] and colostral mononuclear phagocytes are able to kill enteropathogenic Escherichia coli opsonized with human colostral IgA [22]. Thus, there is a possibility that colostrum possess either opsonizing or stimulating effect on phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine IgGs and IgM enhance the phagocytic activity of bovine leucocytes by opsonising bacteria, but IgA lacks such an activity. Human colostrum affects human phagocytes -both inhibition [28] and activation [29] have been reported -and bovine whey proteins may inhibit the phagocytic activity of bovine leucocytes [ 121 but, to our knowledge, there are no reports about their effects on human leucocytes. However, passive immunisation regimens based on bovine colostrum are developed against many microbial diseases and, therefore, interactions between bovine whey proteins and human immune defence cells, e.g.…”
Section: Killing Assaysmentioning
confidence: 99%
“…Their presence in the colostral milk in numbers reciprocal with the maturity of the newborn is an indicator of their importance for the baby's immune defense (Jain et al, 1991). During the early postpartum period when the immune system of the newborn is not fully developed, human colostrum contains a phagocytosis-promoting factor(s), capable of increasing both the number and individual activity of peripheral blood phagocytic cells from normal adults (Straussberg et al, 1995). Moreover, this factor was found to be more active in preterm colostrum, providing reinforcement for the underdeveloped immune system of the preterm newborn.…”
Section: Introductionmentioning
confidence: 99%